Exploring the Effect of Nitrogen, Phosphorus and Potassium Rates of the Nutrient Solution on the Growth and Quality of Common Sowthistle (Sonchus oleraceus L.) Grown Hydroponically - Tzortzakis, Nikos G.; Neofytou, Giannis; Chrysargyris, Antonios (My University, 2025)
Purpose: Wild edible plants, including common sowthistle (Sonchus oleraceus L.), in modern diets presents a promising avenue for dietary diversification due to their specific nutritional profile with increased research interest and potential commercialization. Methods: This study evaluated the effect of different nitrogen (N) concentrations (100–200 mg L− 1; as N100, N200) in combination with different levels (decreased 0.66-fold, normal 1-fold, or increased 1.5-fold) of phosphorus (P; 47-70-105 mg L− 1 as P47, P70, P105) and potassium (K; 250-350-525 mg L− 1 as K250, K350, K525), incorporated in the nutrient solution (NS) for the cultivation of sowthistle in hydroponics. Results: Decreased (0.66-fold) or increased (1.5-fold) P and K levels, under N100 and N200 stimulated plant growth, chlorophylls and carotenoids. In addition, N100 in the NS increased (up to 16%) ascorbic acid content, whereas the combination of N100 and decreased or increased P and K levels resulted in increased (up to 45.5%) flavonoids. In the same P and K rates, phenols and antioxidant capacity were decreased, while N levels modulated this response. Hydrogen peroxide level increased (up to 58.7%) at NPK200 − 70−350 application and coupled with decreases superoxide dismutase activity. Malondialdehyde levels increased (up to 36.1%) at NPK200 − 47−250 application. Increased catalase and peroxidase activities were found in plants grown at NPK100 − 105−525 application. Under the application of N100, the increased rates of P and K positively influenced N uptake, while the application of N200 led to an increase of P content. Conclusions: The modification of P and K in the NS, below or above the levels commonly applied in hydroponics for leafy vegetables, can lead to the stimulation of the growth and quality of sowthistle plants, with benefits to be observed under increased K and P levels at N100 treatment.
Keywords: Hydroponic; Macronutrients; Soilless cultivation; Sowthistle; Wild edible plants